Intrafamilial Occurrence of Hepatitis B Virus Infection in Family Contacts of HBsAg Positive Subject (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Hepatitis B virus (HBV) infection is the global public health challenge. Family members of the HBV infected patients have a high risk of exposure to many blood-borne diseases including Hepatitis B and Hepatitis C viral infections. Of these Hepatitis B is not only the most transmissible infection, but also the only one (HBV) that is preventable by vaccination.Objectives: To assess Occurrence of Hepatitis B Virus Infection in family contacts of HBsAg positive subject.Methods: A six-month cross sectional study was carried out at the department of Medicine, Comilla Medical College. Ethical approval from the institutional review board was obtained to ensure patient privacy and confidentiality.Results: Among 120 selected patients analysis of relatives with the infected patients revealed that most were son and daughters. In the study, out of 379 family members 316(83%) attended the study and 63 (17%) family members were unattended. Among attended family members 37 (11.7%) were known to be positive for HBV, 279 (88.3%) were found negative. Among the study subjects 68 (56.3%) were female and rest 52 (43.8%) were male. Female to male ratio was 1.28:1. Occupation of the study subjects where most were housewives (22.2%) and students (55%). Total 120 index cases, 15 (12.5%) cases were found positive family history for HBV, 90 (75%) were found negative and 15 (12.5%) were unaware of their all family members HBsAg status.Conclusion: Family members staying same house of the HBV infected patients are at highest risk. Total 15(12.5%) index cases were found positive family for HBV infection. So they should take proper preventive measures.J Com Med Col Teachers Asso Jan 2024; 28(1): 14-18